Dizzy [compact disc] (Royal Mountain Records, 2023)
Celebrated alt-pop project Dizzy are back with their new self-titled album, produced by David Pramik (Selena Gomez, chloe moriondo). Singles have been featured by Dork, Line of Best Fit, Under the Radar, Brooklyn Vegan, The Independent, Ones to Watch, and BBC Radio 1 & 2. Dizzy has released two albums so far, 2018's Baby Teeth and 2020's The Sun and Her Scorch. Both albums received critical acclaim and were nominated for Canada's Juno Award for Alternative Album of the Year, which Baby Teeth won.